Database: Enterprise, Skills and Innovation 22nd British National Conference on Databases, BNCOD 22, Sunderland, UK, July 5-7, 2005. Proceedings - Jackson, Mike.; Nelson, David; Stirk, Sue.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
The British National Conference on Databases (BNCOD) was established in 1980 as a forum for research into the theory and practice of databases. The original conference in the series took place at the University of Aberdeen. To be precise, this conference was in fact entitled ICOD which stood for International Conference on Databases. It was the intention, when the series began, that an ICOD would take place every two years, whilst a BNCOD would run in the years in between. As the record shows ICOD was only held in 1980 and 1983. The more junior conference has managed to acquire a lifetime much longer than that of its senior relative! If truth wereknown,however,BNCOD has,overthe years,growninto ICOD and although the conference is still titled (3z(BBritish National,(3y (Bit is, in fact, an international conference that takes place on a yearly basis. Proof of this can be obtained simply by looking at the table of contents of these proceeding which clearlyshowthatthe majorityofpaperspresentedatthis year$1 (Bsconferencecame from contributors whose a?liations are outside the UK. Despitetherangeofpapersono?er,BNCODstillretainsitsuniquelyBritish ?avor. The Programme Committee is drawn from UK academics and the c- ference is always held at a British university (or in earlier years a polytechnic!).s
Invited Paper -- Databases in Grid Applications: Locality and Distribution -- Spatio-temporal Databases -- Spatial Hierarchies and Topological Relationships in the Spatial MultiDimER Model -- Multidimensional Structures Dedicated to Continuous Spatiotemporal Phenomena -- TimeERplus: A Temporal EER Model Supporting Schema Changes -- Data Integration and Information Retrieval -- Semantically Rich Materialisation Rules for Integrating Heterogeneous Databases -- Answering Queries Using Views in the Presence of Functional Dependencies -- LAX: An Efficient Approximate XML Join Based on Clustered Leaf Nodes for XML Data Integration -- Exploitation of Referential Integrity Constraints for Efficient Update of Data Warehouse Views -- Correlation-Based Data Broadcasting in Wireless Networks -- Hierarchical Group-Based Sampling -- Using Schema Transformation Pathways for Data Lineage Tracing -- XML -- XDGL: XPath-Based Concurrency Control Protocol for XML Data -- Updating XML Using Object-Relational Database -- Applied Information Management -- Image Retrieval Using Weighted Color Co-occurrence Matrix -- Street Address Correction Based on Spelling Techniques -- Personalising Patient Information in the Real World -- Republishers in a Publish/Subscribe Architecture for Data Streams.
Keywords: Computer science; Database management; Information storage and retrieval; Computer Science; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Electronic books